Health Monitoring of Invasive Pink Salmon Oncorhynchus gorbuscha in Norway in 2023 - Åse Helen Garseth; Lisa Furnesvik; Kristoffer Vale Nielsen; Anne Berit Olsen; Julie Christine Svendsen; Torfinn Moldal (Aquaculture, Fish and Fisheries)
ABSTRACT Since 2019, the Norwegian Veterinary Institute (NVI) has conducted health monitoring of pink salmon in Norway. The primary purpose of health monitoring has been to examine the presence of selected notifiable infections in pink salmon, but also to gain general knowledge regarding the health of pink salmon to inform assessments of risks to wild and farmed native salmonids. In 2023, post‐mortem examinations were performed on 184 pink salmon captured in rivers Lakselv, Tana, Neiden, Komagelva, Kongsfjordelva and Karpelv in the County of Finnmark, Norway. Tissue samples from 161 of these were analysed with specific PCR assays aimed at detecting infectious salmon anaemia virus (ISAV), viral haemorrhagic septicaemia virus (VHSV), infectious hematopoietic necrosis virus (IHNV), piscine orthoreovirus genotype 1 (PRV‐1) and Renibacterium salmoninarum. In addition, cultivation methods were applied to detect the presence of cultivable virus and bacteria. ISAV, VHSV, IHNV PRV‐1 and R. salmoninarum were not detected by PCR. Furthermore, R. salmoninarum, Aeromonas salmonicida subsp. salmonicida and cultivable virus were not detected by cultivation. With the exception of the absence of PRV‐1, the results correspond to previous years' health‐monitoring projects.